Export promotion policies and the crowding-out effect in developing countries - Mat Ghani, Gairuzazmi (Blackwell, 2006)
Critics of export promotion policies have pointed out a fallacy of composition, where what is viable for a small country acting in isolation might not be viable when pursued by a group of countries simultaneously. This paper investigates the crowding-out effect of the fallacy of composition; that is, whether developing countries that specialize in exports of manufactured products compete and crowd out one another's exports. The results of fixed-effects panel estimation suggest that developing countries are not crowding out one another's exports. Instead, they are crowding out Western European countries' exports of manufactured products.